Community-Based Ecotourism Potential In The Jatigede Reservoir Area, Sumedang District - Latif, B Syarifuddin; Asyari; Azhari, Alfin Fauzi (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2024)
The reservoir area is part of the reservoir area which is a combination of highlands and water areas. Tourism activities in ecotourism that prioritize natural beauty, activities, and several attractions are the main attractions. This community service aims to identify the ecotourism potential of the Jatigede Reservoir and the ecotourism management plan for the Jatigede Reservoir community. Community service locations are in the Wado, Darmaraja, and Jatigede Districts. Community service informants are community members and stakeholders at the village and sub-district levels. The results of community service show that the Jatigede Sumedang Reservoir has potential community resources to be developed into eco-tourism. A number of tourist attractions include marine tourism, ecotourism, cultural and arts tourism, agrotourism, sports tourism, campsites, and pilgrimage routes. Therefore, community policies are needed to develop ecotourism. The author encourages full community participation in planning and managing ecotourism in accordance with the needs and culture of local communities.